Análise do discurso securitário à luz dos postulados da criminologia crítica - Casarin, Ana (2020)
This research aims to examine the prevailing punitive narratives around public safety, adopting the paradigm of Critical Criminology and its theoretical framework as a basis for a compilation of the most important criticism of the concept of safety and how it has been used to justify the exercise of punitive power. It raises questions about the evolution of the narratives that aim to legitimize the power to punish throughout History, seeking to draw a parallel with the construction of the concept of safety. Two theoretical models are presented: one that is conservative, authoritarian and exclusionary, and an alternative one, that focus on a more democratic and inclusionary ideal of safety. It identifies the prevalence, in the contemporary world, of an authoritarian model for the creation of public safety policies, which identifies public safety only with the prevention and repression of some types of crime. Starting from this point, it was possible to reflect on the relationship between the logic of the Criminal Law of the Enemy – which, as described throughout this paper, has been a constant in the punitive power since ancient times –, and the reproduction and maintenance of a conservative approach to the development of public policies for safety that that results in the criminalization, exclusion, and extermination of certain social groups